Implementación de solución tecnológica para el instituto nacional de higiene “leopoldo izquieta pérez” basado en la guía pmbok - Solano Morales, Oswaldo (2011)
The project consists of applying the methodology PMI (Project Management Institute) in the management and control of the project to implement technology solutions at the National Institute of Hygiene and Tropical Medicine "Leopoldo Izquieta Pérez." For this proposed project and thesis topic we have focused on the application of PMBOK (PMI guidebook) for direction, with its main objective being the IT strengthening of the INHMT.